An examination of the saturation microstructures achieved in ultrafine-grained metals processed by high-pressure torsion - Shima Sabbaghianrad (Journal of Materials Research and Technology, 2014)
Experiments were conducted on two commercial alloys, a Cu–0.1%Zr alloy and an Al-7075 aluminum alloy, to investigate the significance of the saturation microstructure which is achieved after processing by high-pressure torsion (HPT). Samples were processed by HPT and also by a combination of equal-channel angular pressing (ECAP) followed by HPT. The results show that the saturation conditions are dependent upon the grain size in the material immediately prior to the HPT processing. Additional grain refinement may be achieved in HPT by initially processing the material to produce an ultrafine-grain size before conducting the processing by HPT.